PENGARUH PERSEPSI HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK TEH JAVANA DI OKE SWALAYAN TG.MORAWA - Nanda Syafriliani; Sari Wulandari; M. Guffar Harahap (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2022)
This study aims to determine the effect of price perception and product quality on purchasing decisions for Javana tea products at Oke Swalayan Tanjung Morawa. This study uses a quantitative descriptive approach, aiming to determine the relationship between two or more variables. The population of this research is the consumers of Oke Swalayan Tanjung Morawa during the month of April as many as 1208 consumers. The sampling technique used is non-probability sampling, namely by accident. Researchers used a sample determination based on the Slovin formula and 92 respondents were used as research samples in this study. The analysis technique used is multiple regression analysis. The suitability test using the t test and f test as well as the coefficient of determination test. The results of the analysis obtained the value of t arithmetic for the variable Price Perception (X1) of 2.449. Then the calculated t obtained is greater than the t table value or 2.449 > 1.662 then it is also seen that the sig value is smaller than the probability value of 0.05 or 0.016 < 0.05. So it can be concluded that the price perception variable has a positive and significant effect on purchasing decisions. The results of the analysis obtained the t value for the Product Quality variable (X2) of 8,969. Then the calculated T obtained is greater than the T table value or 8.969 > 1.662 then it is also seen that the sig value is smaller than the probability value of 0.05 or 0.000 < 0.05. So it can be concluded that the Product Quality variable has a positive and significant effect on Purchase Decisions. Based on the simultaneous test, it can be seen that the calculated f value is 50,796 with a sig level of 0.000, therefore the sig value is 0.000 > 0.05 and the calculated F value is 50,796 > F table 3.10. This shows that the independent variables X1, and X2 simultaneously have a positive and significant effect on the variables. dependent Y. R square (R2) or the square of R shows the determinant coefficient is 0.533, meaning that the percentage contributed by Price Perception (X1) and Product Quality (X2) to Purchase Decision (Y) is 53.3%, while the remaining 46.7% is influenced by other variables which were not investigated by this study